2001
DOI: 10.1002/car.688
|View full text |Cite
|
Sign up to set email alerts
|

Children's response to the medical visit for allegations of sexual abuse: maternal perceptions and predicting variables

Abstract: This study examined maternal perceptions of their child's response to the medical evaluation for alleged sexual abuse. A total of 50 mothers were interviewed 6 months after a visit to a Child Protection Clinic for a medical evaluation of alleged sexual abuse. The mothers answered a questionnaire on their child's reactions to the medical visit. More than 60% of children were perceived as being reassured about physical integrity. The degree of psychological distress was independent of perpetrator's identity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Similarly to Allard‐Dansereau, 33 our findings suggested that physician behaviour had an influence on the child's degree of distress. The emphasis parents and children placed on staff attitudes, explanations offered and the relationship between doctor and child has implications for clinician training and practice.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Similarly to Allard‐Dansereau, 33 our findings suggested that physician behaviour had an influence on the child's degree of distress. The emphasis parents and children placed on staff attitudes, explanations offered and the relationship between doctor and child has implications for clinician training and practice.…”
Section: Discussionsupporting
confidence: 72%
“…Allard‐Dansereau et al. 33 made a similar finding. This suggests that is it the very fact that there was abuse (rather than the specific details) and that a medical is needed (rather than what the doctor actually does) that is stressful for parent and child.…”
Section: Discussionmentioning
confidence: 67%
“…Later studies have reported less negative responses to the ano‐genital examination. Allard‐Dansereau, Tremblay, & Bernard‐Bonnin (2001) explored maternal perceptions of their child's reaction to the medical evaluation for alleged sexual abuse and found more than 60% of children were perceived by their mothers as being reassured regarding physical integrity. A total of fifty mothers of male and female children between the ages of 4 and 12 years were interviewed six months after their child was seen for a medical examination for child sexual abuse.…”
Section: Review Of the Related Literaturementioning
confidence: 99%
“…In New Zealand, Davies et al () demonstrated that post CSA medical examination, 42.9 per cent ( n = 9) of children reported feeling a ‘bit better’ but 23.8 per cent felt ‘worse’, with negative responses reflecting a perceived lack of choice or preparation for medical examination. Allard‐Dansereau et al (), in Canada, found that 62 per cent of mothers felt reassured about the physical condition of their child following examination, with ‘kindness’ of the physician as a factor in alleviating the impact of the examination. ‘Reassurance’ (that serious harm has not been caused) as a purpose of examination is supported by Mears et al () in the USA, with 78 per cent of children aged 11–17 years ( n = 77) stating that medical examination was ‘helpful’ and made them ‘feel better’.…”
Section: Introductionmentioning
confidence: 99%